Lobbying and Incentives for Legislative Organization - Daniel Diermeier; Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
Formal theories of the internal organization of legislatures have mainly focused on the United States Congress. While these models have been successful in showing why committee systems should emerge in Congress, they fail to explain the variance in internal organization across legislatures which is indicated by the comparative study of legislative politics. To analyze the effects of different constitutional features on the organizational choices of legislatures we adopt a vote-buying model (Groseclose and Snyder 1994) and then consider the incentives to delegate decision rights in a multi-chamber noncooperative game. Our main result states that multi-cameral legislatures encourage the existence of internal veto players or super-majority rules, while unicameral bodies provide incentives to delegate power to a single actor such as a prime minister or party leader.
Keywords: 330